Population estimates and determinants of severe maternal thinness in India. Issue 3 (1st November 2021) - Choedon, Tashi; Sethi, Vani; Chowdhury, Ranadip; Bhatia, Neena; Dinachandra, Konsam; Murira, Zivai; Bhanot, Arti; Baswal, Dinesh; de Wagt, Arjan; Bhargava, Madhavi; Meshram, Indrapal Ishwarji; Babu, Giridhara R.; et al.
Abstract: Objective: To examine prevalence, risk factors, and consequences of maternal severe thinness in India. Methods: This mixed methods study analyzed data from the Indian National Family Health Survey (NFHS)‐4 (2015–2016) to estimate the prevalence of and risk factors for severe thinness, followed by a desk review of literature from India. Results: Prevalence of severe thinness (defined by World Health Organization as body mass index [BMI] <16 in adult and BMI for age Z score < –2 SD in adolescents) was higher among pregnant adolescents (4.3%) compared with pregnant adult women (1.9%) and among postpartum adolescent women (6.3%) than postpartum adult women (2.4%) 2–6 months after delivery. Identified research studies showed prevalence of 4%–12% in pregnant women. Only 13/640 districts had at least three cases of severely thin pregnant women; others had lower numbers. Three or more postpartum women aged ≥20 years were severely thin in 32 districts. Among pregnant adolescents, earlier parity increased odds (OR 1.96; 95% CI, 1.18–3.27) of severe thinness. Access to household toilet facility reduced odds (OR 0.72; 95% CI, 0.52–0.99]. Among mothers aged ≥20 years, increasing education level was associated with decreasing odds of severe thinness (secondary: OR 0.74; 95% CI, 0.57–0.96 and Higher: OR 0.54; 95% CI, 0.32–0.91, compared with no education); household wealth and caste were also associated with severe thinness. Conclusion: This paper reveals the geographic pockets that need priority focus for managing severe thinness among pregnant women and mothers in India to limit the immediate and intergenerational adverse consequences emanating from these deprivations. Synopsis: This article reveals the geographic pockets in India that need priority focus for managing severe thinness among pregnant and postpartum women to limit the immediate and intergenerational adverse consequences emanating from these deprivations.